HEMODIALYSIS IN UKRAINE (2006-2015 YEARS) - M. O. Kolesnyk; N. O. Saidakova; N. I. Kozlyuk; S. S. Nikolaenko; L.M. Snisar (Ukrainian Journal of Nephrology and Dialysis, 2017)
We used the data of “National Register of CKD Patients ” which is formed annually by SI “Institute of Nephrology NAMS of Ukraine”. The results demonstrate the low level of availability of medical care